The The Use of Fine Art Activity Strategies in Mastering Vocabulary at Al-Hidayah Boarding School Depok West Java - Nur Alifia (Universitas Cokroaminoto Palopo, 2022)
Art is a person's creative phenomenon to express themselves in an event. It can be found in music, by hand, in the appearance of drama, or even in vocal sports. In learning, students often find problems that originate within themselves or originate in their environment. The problems that originate within themselves can be a lack of interest in reading, a lack of vocabulary, or a shortage of visual aids that make it easier for them to grasp science. The purpose of this study in al-Hidayah. Boarding School is to learn the arts of fine arts strategy for effectively mastering vocabulary. The methods used in this scientific work are those of quantitative research, data exploration, experimental design, and survey. Experiments were carried out to reinforce the initial hypothesis that with fine arts, vocabulary study was easier to understand. Surveys provide excellent databases for scientific reference. As for the results of this study being a fine art strategy for mastering vocabulary effectively, students can understand the vocabulary learned from teachers, and they can choose their way to select the correct vocabulary in translating, antonyms, word translations, or hyponyms.